Plan de estudios y práctica profesionalizante en el cuidado enfermero y sus competencias. - Carina Benito, María (Visión de Enfermería Actualizada, 2020)
This research focuses on the comparative analysis of the Nursing Career Curriculum and the evaluations that teachers perform during the professionalizing practices of the students, in order to detect the points of coincidence and the possible incongruities between them. On the one hand, the various components of the curriculum and the concepts related to nursing care and the skills required to provide such care are analysed; on the other hand, their explanation in the evaluations of the professionalizing practice.